Examining the Patterns of Goodwill Impairments in Europe and the US. (1st September 2016) - André, Paul; Filip, Andrei; Paugam, Luc
Abstract: We examine the patterns of goodwill impairments in Europe and in the US over the period from 2006 to 2015, for a sample of more than 35, 000 firm-year observations. We define the timeliness of goodwill impairments as the frequency of accounting impairments conditional to indications of economic impairments. We measure indications of economic impairment with three metrics: equity market value minus equity book value less than goodwill, market-to-book smaller than one and negative earnings before interest, tax, depreciation and amortisation (EBITDA). Our research strategy leads us to draw very different conclusions than those in the recent EFRAG (2016) study. While median levels of goodwill on the books between US and European firms are relatively similar, we find several indications that US firms recognise timelier impairments, at least during 2008 and 2009, that is, the early years of the financial crisis. We further document that US impairers write down a much greater percentage of their beginning balance of goodwill than European impairers. During the financial crisis, the median level of impairment by US firms was 63% of opening goodwill in 2008 and 40% in 2009, whereas median European write-downs were only 6% and 7% of opening goodwill, respectively. Even though European firms are more likely to impair over multiple years, the cumulative impairments never come close to the level of US firms, be it in a single year or cumulative over multiple years. We also find that the frequency of accounting impairment is small compared to the number of firms presenting evidence of economic impairment: only 20–25% of firms recognise impairments depending on the measure of economic impairment. This has often been interpreted by academics as a sign of untimely write-offs. Accounting differences between US Generally Accepted Accounting Principles and International Financial Reporting Standards are unlikely to explain our results. One caveat of our analysis is that it does not allow us to draw conclusions on whether the observed differences between US and European firms are driven by differences in conditional conservatism and/or big bath accounting practices.